2006
DOI: 10.1021/pr060177d
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Glycoproteomic Approach Involving Lysine Derivatization for Structural Characterization of Recombinant Human Erythropoietin

Abstract: Lysine-containing peptides comprising glycosylation sites derived from recombinant human erythropoietin (rHuEPO) by trypsin or Lys-C and PNGase F dual digestion were derivatized with 2-methoxy-4,5-dihydro-1H-imidazole and its deuterated analogues. In the same reaction, under reducing conditions (beta-mercaptoethanol), cysteines were converted into methyl-cysteines and lysines into Lys-4,5-dihydro-1H-imidazole. Both modifications on cysteines and lysines simplified the CID-MS/MS spectra, while preserving the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Consequently, protease digest of rhEPO may be a good model sample for the present study. Although similar attempts using the RP (C18 and C4)-HPLC have already been reported [12,13], to the best of our knowledge, there has been little investigation of HILIC or ZIC-HILIC separation for rhEPO glycopeptides and other complex mixtures of both N-and O-glycopeptides. In the present work, 105 N-glycopeptides and 8 O-glycopeptides were detected during a single run of the capillary ZIC-HILIC/ESI MS analysis using 150 ng rhEPO.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consequently, protease digest of rhEPO may be a good model sample for the present study. Although similar attempts using the RP (C18 and C4)-HPLC have already been reported [12,13], to the best of our knowledge, there has been little investigation of HILIC or ZIC-HILIC separation for rhEPO glycopeptides and other complex mixtures of both N-and O-glycopeptides. In the present work, 105 N-glycopeptides and 8 O-glycopeptides were detected during a single run of the capillary ZIC-HILIC/ESI MS analysis using 150 ng rhEPO.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several new methods for the purification/ enrichment of glycopeptides (e. g., chemical trapping [7,8], sepharose adsorption [9], and SPE using porous graphite carbon (PGC) [10] or zwitterionic-type hydrophilic interaction chromatography (hereafter called ZIC-HILIC) [11]) have been developed. Selective separation methods of glycopeptides using RP [12,13] and HILIC [14 -16] columns have also been reported. Very recently, we reported that a ZIC-HILIC column with sulfobetaine groups [17] has a high capability for separation based on its structural recognition of N-glycans and selectivity for N-glycopeptides [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of tryptic peptide fragments [26,30] The desired bands were excised from the SDS-polyacrylamide gel or 2D gel, and dried by the sequential procedures of destaining with (NH 4 )HCO 3 (50 mM in 50% [v/v] CH 3 CN) to remove the Coomassie Brilliant Blue, dehydration with CH 3 CN (50 μL), and drying with a SpeedVac to produce a white solid. A reducing reagent (10 mM DTT in 50 mM (NH 4 )HCO 3 ) was then added to the gel slices at 50°C for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…Then 1.3 µL of Triton X‐100 and 1.0 µL of PNGase F were added to the reaction. Proteolysis time lasted for 3 h at 37°C 27, 28…”
Section: Methodsmentioning
confidence: 99%